Developing indicators of local governance in the Philippines towards an "ISO" for LGUs - Brillantes, Alex B., Jr. (2001)
The importance of setting standards for local governments is manifested by the various performance measurement systems that have been initiated by different sectors, including the national government through the Department of the Interior and Local Government, the academe, various non-governmental organizations and other institutions that are supported by donor and international agencies such as United States Agency for International Development (USAID) and the United Nations Development Program (UNDP). And with the development of the International Standards Organization (ISO) certifications for generic management system standards in the private sector, there is a move to apply this ISO concept and framework for local governments to attest that they have passed this set of performance-related standards. The paper discusses the participatory nature of the development of appropriate measures and indicators of good governance at the local level. The effort of the various stakeholders in local governance to develop performance criteria has largely been related to the development of performance indicators and performance measures. The paper proposes the ten major indicators of effective local governance, which were developed by local government officials themselves after a series of workshops were held throughout the country. These indicators are broken down into specific activities to serve as a checklist. Finally it enumerates several issues and challenges in the implementation of these performance measurements, including the issue of convergence of all the efforts in the performance measurement of local governments.
Keywords: Good governance indicators; Government productivity -- Evaluation; Good governance; Local governance; Performance evaluation; International Standards Organization (ISO)